King's Parkinson's disease pain scale, the first scale for pain in PD: An international validation. Issue 12 (11th June 2015) - Chaudhuri, K. Ray; Rizos, A.; Trenkwalder, C.; Rascol, O.; Pal, S.; Martino, D.; Carroll, C.; Paviour, D.; Falup‐Pecurariu, C.; Kessel, B.; Silverdale, M.; Todorova, A.; et al.
Abstract Pain is a key unmet need and a major aspect of non‐motor symptoms of Parkinson's disease (PD). No specific validated scales exist to identify and grade the various types of pain in PD. We report an international, cross‐sectional, open, multicenter, one‐point‐in‐time evaluation with retest study of the first PD‐specific pain scale, the King's PD Pain Scale. Its seven domains include 14 items, each item scored by severity (0‐3) multiplied by frequency (0‐4), resulting in a subscore of 0 to 12, with a total possible score range from 0 to 168. One hundred seventy‐eight PD patients with otherwise unexplained pain (age [mean ± SD], 64.38 ± 11.38 y [range, 29‐85]; 62.92% male; duration of disease, 5.40 ± 4.93 y) and 83 nonspousal non‐PD controls, matched by age (64.25 ± 11.10 y) and sex (61.45% males) were studied. No missing data were noted, and floor effect was observed in all domains. The difference between mean and median King's PD Pain Scale total score was less than 10% of the maximum observed value. Skewness was marginally high (1.48 for patients). Factor analysis showed four factors in the King's PD Pain Scale, explaining 57% of the variance (Kaiser‐Mayer‐Olkin, 0.73; sphericity test). Cronbach's alpha was 0.78, item‐total correlation mean value 0.40, and item homogeneity 0.22. Correlation coefficients of the King's PD Pain Scale domains and total score with other pain measures were high. Correlation with the Scale for Outcomes in PD‐Motor, Non‐Motor Symptoms Scale total score, and quality of life measures was high. The King's PD Pain Scale seems to be a reliable and valid scale for grade rating of various types of pain in PD. © 2015 International Parkinson and Movement Disorder Society